Perbedaan Kekuatan Tekan (Compressive Strength) Resin Komposit Nanofill Antara Teknik Inkremental dan Teknik Bulk Fill - Afsari, Inggrid Ganarsih, drg. Noor Hafida W., Sp.KG (2016)
Composite resin is a commonly used restoration material used in dental practice. This particular material is widely requested due to its esthetic value. Composite resin is more used than amalgam materials, even for posterior teeth restoration. This study is aimed to determine the most effective technique in using nanofill composite resin. This study uses acrylic casts with a 6 mm diameter and 6 mm height. A total of 32 samples were divided to 2 groups, each with 16 samples. The first group applied the incremental technique, while the second group applied bulk fill. Samples were soaked in aquades and incubated for 24 hours in a temparature of 370 C. A universal testing machine (UTM) were used to test their compressive strength on a rate of 1 mm/minute with load 100 ton. Obtained data were analyzed using independent t-test. The results showed a significant difference of compressive strength between the two groups p=0,000, (p<0,05), with the incremental group having a higher compressive strength than the bulk fill group.